Attraction strategies for the unsought services industry : case on the automobile repair and servicing industry. - Soh, See Woon. (2008)
This research aims to design attraction strategies in one of the sector of the unsought services industry-the automobile repair and servicing industry. It seeks to understand the characteristics of the automobile repair and servicing industry thereby proposing communication strategies to solve the problem of attracting customers, which is an issue generic to all unsought services.